Composite positive electrode lithium supplement additive and preparation method and application thereof

By adopting the Li2NixCu(1-x)O2@Li3PO4@C composite structure in the nickel-cubate lithium co-extracting agent, the problems of high residual alkali content and poor electrochemical performance of the lithium co-extracting agent in the prior art are solved, and higher electrochemical performance and cycle stability are achieved.

CN120089743APending Publication Date: 2025-06-03HEFEI GUOXUAN HIGH TECH POWER ENERGY
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202510223086.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-02-27
Publication Date
2025-06-03

AI Technical Summary

Technical Problem

In the prior art, the lithium nickel-copperate positive electrode lithium supplement agent has problems such as high residual alkali content on the surface, poor processing performance and poor electrochemical performance.

Method used

A composite positive electrode lithium supplement additive is used, which includes the matrix Li2NixCu(1-x)O2, Li3PO4 cladding and conductive polymer cladding from the inside to the outside. The combination of the matrix, a phosphate cladding and a conductive polymer cladding is prepared by co-precipitation method to improve the electrochemical performance and stability of the lithium supplement agent.

Benefits of technology

It effectively reduces the residual alkali content on the surface of lithium nickel-cubate, improves ionic conductivity and electrochemical properties, and enhances the cyclic stability of the material.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005289327510000081
    Figure BDA0005289327510000081
  • Figure BDA0005289327510000082
    Figure BDA0005289327510000082
  • Figure BDA0005289327510000091
    Figure BDA0005289327510000091
Patent Text Reader

Abstract

The invention discloses a composite positive electrode lithium supplement additive and a preparation method and application thereof. The composite positive electrode lithium supplement additive sequentially comprises a substrate, a first coating layer (Li3PO4 layer) coated on the surface of the substrate and a second coating layer (conductive polymer layer) coated on the surface of the first coating layer from inside to outside, the material of the substrate is Li2NixCu (1-x) O2, and x is more than or equal to 0.6 and less than 1. According to the composite positive electrode lithium supplement additive, NixCu (1-x) (OH) 2 is prepared through a coprecipitation method, then the NixCu (1-x) (OH) 2 is mixed with a lithium source to be sintered to obtain a matrix, the matrix is uniform in component, and the content of residual alkali on the surface of Li2NixCu (1-x) O2 can be well reduced; the phosphate coating layer can provide a transmission channel for lithium ions, so that the ionic conductivity is improved; the conductive polymer coating layer not only can effectively improve the conductivity of the matrix, but also can effectively prevent the matrix from being in contact with moisture, carbon dioxide, oxygen and the like in air, so that the cycling stability of the material is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of lithium - ion batteries, and particularly relates to a composite cathode lithium - supplementing additive, a preparation method thereof, and an application thereof. Background Art

[0002] As a new type of high - energy battery, lithium - ion batteries have been widely used in new - energy electric vehicles and electrochemical energy storage fields in recent years. This also puts forward higher requirements for the energy density, safety, cycle performance, rate performance, and high - and low - temperature performance of lithium - ion batteries.

[0003] During the first charging process of lithium - ion batteries, a solid electrolyte interface (SEI) film is formed on the electrode surface due to the decomposition of the electrolyte, resulting in a low Coulombic efficiency in the first cycle of the battery and a reduction in the battery energy density. To solve the problem of low first - cycle efficiency, the existing main methods include lithium - supplementing at the positive electrode and the negative electrode. Lithium - supplementing at the negative electrode usually requires the use of highly active lithium powder or lithium foil, which not only has high requirements for equipment and working environment, but also has high risks and uneven lithium - supplementing. Compared with the high - difficulty and high - investment negative - electrode lithium - supplementing process, positive - electrode lithium - supplementing is safer. A typical positive - electrode lithium - supplementing process is to add a small amount of high - capacity positive - electrode material during the positive - electrode slurry mixing process. During the charging process, the excess Li element is released from these high - capacity positive - electrode materials and embedded into the negative electrode to supplement the irreversible capacity of the first charge - discharge.

[0004] It is reported that lithium nickel copper oxide (Li 2 Ni x Cu (1-x) O 2 ) is a reliable lithium - supplementing additive with high charging capacity and irreversible capacity, and is expected to meet the performance requirements of the lithium - supplementing agent. However, in traditional technologies, the method of preparing the lithium - supplementing agent by dry - mixing raw materials followed by sintering has problems such as uneven particle size of the sintered material, high surface residual alkali content, poor stability in air, poor conductivity of the finished lithium - supplementing additive, and insufficient electrochemical performance. Summary of the Invention

[0005] The main purpose of the present invention is to provide a composite cathode lithium - supplementing additive and a preparation method thereof, so as to solve the problems of high surface residual alkali content, poor processing performance, and sub - optimal electrochemical performance of the lithium nickel copper oxide cathode lithium - supplementing agent in the prior art.

[0006] To achieve the above - mentioned purpose, the present invention adopts the following technical solutions:

[0007] In the first aspect, the present invention provides a composite cathode lithium - supplementing additive.

[0008] The composite cathode lithium supplement additive provided by the present invention sequentially includes, from the inside to the outside: a matrix, a first coating layer coated on the surface of the matrix, and a second coating layer coated on the surface of the first coating layer; wherein, the material of the matrix is Li 2 Ni x Cu (1-x) O 2 , where the value of x can be taken as 0.6 ≤ x < 1; the first coating layer is a Li 3 PO 4 layer, and the second coating layer is a conductive polymer layer; the general formula of the composite cathode lithium supplement can be expressed as Li 2 Ni x Cu (1-x) O 2 @Li 3 PO 4 @C, where C represents a conductive polymer.

[0009] For the above-mentioned composite cathode lithium supplement additive, its matrix components are uniform, which can well reduce the residual alkali content on the surface of Li 2 Ni x Cu (1-x) O 2 ; the phosphate coating layer can provide a transmission channel for lithium ions to improve the ionic conductivity; the conductive polymer coating layer can not only effectively improve the conductivity of the matrix, but also effectively block its contact with moisture, carbon dioxide, oxygen, etc. in the air, thereby improving the cycle stability of the material.

[0010] Furthermore, the matrix is spherical or quasi-spherical particles, and its particle size D50 is 3 - 8 μm, specifically such as D 50 = 4 μm.

[0011] Furthermore, the mass of the Li 3 PO 4 layer is 1 wt% - 3 wt% of the mass of the matrix, specifically such as 1 wt%, 2 wt% or 3 wt%.

[0012] Furthermore, the mass of the conductive polymer layer is 1 wt% - 5 wt% of the total mass of the matrix and the first coating layer, specifically such as 1 wt%, 3 wt% or 5 wt%.

[0013] Furthermore, the conductive polymer can be selected from one or more of: polyacetylene, polypyrrole, polyaniline, polythiophene, polyfuran, polydopamine and their derivatives.

[0014] Furthermore, the value of x can be taken as 0.8 ≤ x < 1, specifically such as 0.6, 0.8 or 0.9.

[0015] In the second aspect, the present invention provides a preparation method of the composite cathode lithium supplement in the first aspect.

[0016] The preparation method of the composite cathode lithium supplement additive provided by the present invention includes the following steps:

[0017] Step S1, preparation of the matrix material nickel copper lithium acid precursor Ni x Cu (1-x) (OH) 2 ;

[0018] Step S2, mixing and sintering the matrix nickel copper lithium acid precursor Ni x Cu (1-x) (OH) 2 with a lithium source to obtain a Li 2 Ni x Cu (1-x) O 2 matrix;

[0019] Step S3, dispersing the Li 2 Ni x Cu (1-x) O 2 matrix and phosphate in solvent 1, drying and sintering to obtain Li 2 Ni x Cu (1-x) O 2 @Li 3 PO 4 ;

[0020] Step S4, dispersing the Li 2 Ni x Cu (1-x) O 2 @Li 3 PO 4 and the conductive polymer in solvent 2 for ball milling and spray drying to obtain Li 2 Ni x Cu (1-x) O 2 @Li 3 PO 4 @C, that is, the composite cathode lithium supplement additive.

[0021] Furthermore, in step S1, the preparation steps of the matrix material nickel copper lithium acid precursor Ni x Cu (1-x) (OH) 2 are as follows:

[0022] (1) Prepare a mixed salt solution of Ni and Cu using soluble nickel salts and soluble copper salts in a predetermined molar ratio of Ni:Cu = x:1 - x, where 0.6 ≤ x < 1, preferably 0.8 ≤ x < 1, to obtain a total metal ion concentration of the mixed salt solution of 1 - 2 mol / L; prepare an alkali solution with a concentration of 2 - 4 mol / L and an ammonia water solution with a concentration of 1 - 2 mol / L.

[0023] (2) Under a protective atmosphere, prepare a reaction bottom solution with a pH value of 11 - 12 and an ammonia concentration of 2 - 4 g / L in a reaction kettle, control the reaction temperature to be maintained at 50 - 60 °C, and the stirring intensity to be 400 - 600 rpm; then simultaneously pump the mixed salt solution of Ni and Cu, the alkali solution, and the ammonia water solution into the reaction kettle for coprecipitation reaction; in the first stage of the coprecipitation reaction, control the pH range to slowly decrease between 10.6 and 12, keep the ammonia concentration unchanged at 2 - 4 g / L, and control the growth of the precursor particles; when it is detected that the precursor particle D 50 reaches 70% - 90% of the target particle size, enter the second stage of the coprecipitation reaction, control the pH value to remain unchanged, and the ammonia concentration to be 1 - 2 g / L, and control the growth of the precursor particles; when it is detected that the precursor particle D 50 reaches the target particle size of 3 - 8 μm, stop feeding, and after aging, separating, washing, drying, sieving, and demagnetizing, the nickel - copper lithium acid lithium precursor of the matrix material is obtained.

[0024] Further, the soluble nickel salt can be one or more of nickel sulfate hydrate, nickel chloride, and nickel nitrate hydrate, the soluble copper salt is one or more of copper sulfate, copper chloride, and copper nitrate hydrate, and the alkali solution is one or a mixture of sodium hydroxide and potassium hydroxide solutions;

[0025] Further, the flow rate of the mixed solution of Ni and Cu metal salts is 20 mL / min, the flow rate of the alkali solution is 12 - 13 mL / min, and the flow rate of the ammonia water is 5 - 6 mL / min.

[0026] Further, in step S2, the lithium source is selected from one or more of lithium hydroxide, lithium carbonate, and lithium oxide; the dosage of the lithium source is added in a ratio of (Ni + Cu):Li molar ratio of 1:1.9 - 2.05; the gas used for sintering is selected from one or more of nitrogen, argon, carbon monoxide, and hydrogen;

[0027] Further, in step S2, the sintering conditions are: first pre - sinter at 350 - 450 °C for 4 - 8 h, and then sinter at 600 - 700 °C for 10 - 18 h.

[0028] Further, in step S3, the phosphate is one or more of ammonium monohydrogen phosphate, ammonium dihydrogen phosphate, and ammonium triammonium phosphate; the added mass of the phosphate is Li2 Ni x Cu (1-x) O 2 1 to 3% of the matrix mass; the solvent 1 is one or more of ethanol, methanol, and propanol; the gas used for sintering is selected from one or more of nitrogen, argon, carbon monoxide, and hydrogen; the sintering conditions are: sintering at 400 - 600 °C for 4 - 8 h.

[0029] Further, in step S4, the drying is spray drying, and the parameters of spray drying are: the inlet temperature is 280 - 300 °C, the outlet temperature is 110 - 120 °C, and the gas flow rate is 4 - 6 m 3 / h; the solvent 2 is one or more of ethanol, methanol, and propanol; the addition amount of the conductive polymer is Li 2 Ni x Cu (1-x) O 2 @Li 3 PO 4 1 wt% - 5 wt% of the mass; the conductive polymer can be one or more of polyacetylene, polypyrrole, polyaniline, polythiophene, polyfuran, polydopamine, and their derivatives.

[0030] In the third aspect, the present invention provides a positive electrode plate.

[0031] The positive electrode plate provided by the present invention includes the composite positive electrode lithium supplement additive described in the first aspect of the present invention, or the composite positive electrode lithium supplement additive prepared by the method described in the second aspect of the present invention.

[0032] In the fourth aspect, the present invention provides a lithium - ion battery.

[0033] The lithium - ion battery provided by the present invention includes a positive electrode, a negative electrode, and an electrolyte, wherein the positive electrode is the positive electrode plate described above in the present invention.

[0034] In the fifth aspect, the present invention provides an electronic device.

[0035] The electronic device provided by the present invention includes the battery provided in the fourth aspect of the present invention.

[0036] Compared with the prior art, the present invention has the following beneficial effects:

[0037] The lithium - supplementing additive precursor prepared by the coprecipitation method first has excellent sphericity, easy - to - control particle size, good homogenization, and a simple preparation process, which is suitable for large - scale production. After being mixed and calcined with a lithium source, the obtained lithium - supplementing additive for the nickel - copper - lithium - based cathode has good component homogenization and better electrochemical performance. Phosphate can react with the residual alkali on the surface of nickel - copper - lithium to form lithium - containing phosphate. On the one hand, this reaction can consume and reduce the residual alkali, and on the other hand, the generated lithium - containing phosphate can provide a transmission channel for lithium ions, improve the ionic conductivity, and prevent the direct contact between the cathode surface and the electrolyte, effectively preventing the erosion of HF, thereby inhibiting the formation of side reactions and resistive surface films. The conductive polymer coating layer can not only effectively improve the conductivity of the nickel - copper - lithium matrix, but also effectively block the contact between the nickel - copper - lithium and moisture, carbon dioxide, oxygen, etc. in the air, avoiding the deterioration of nickel - copper - lithium due to oxidation and reaction. In the battery system, it can also reduce the contact area between the nickel - copper - lithium and the electrolyte, avoiding the occurrence of side reactions and the dissolution of Ni and Cu elements, thereby improving the cycle stability of the material. Description of the Drawings

[0038] Figure 1 It is an electron microscope photograph of the matrix precursor of the lithium - supplementing additive in Example 1 magnified 10000 times.

[0039] Figure 2 It is an electron microscope photograph of the matrix of the lithium - supplementing additive in Example 1 magnified 10000 times.

[0040] Figure 3 It is an electron micrograph of the composite lithium - supplementing additive in Example 1 magnified 10000 times. Detailed Embodiments

[0041] The present invention will be further described in detail below in conjunction with the specific embodiments. The provided embodiments are only for clarifying the present invention, rather than limiting the scope of the present invention. The following provided embodiments can be used as a guide for those of ordinary skill in the art to make further improvements, and do not limit the present invention in any way.

[0042] The experimental methods in the following embodiments, unless otherwise specified, are all conventional methods, carried out according to the techniques or conditions described in the literature in this field or according to the product specifications. The materials, reagents, etc. used in the following embodiments, unless otherwise specified, can all be obtained from commercial channels.

[0043] Example 1

[0044] Step S1, preparation of the matrix material nickel - copper - lithium - based precursor Ni x Cu (1-x) (OH) 2 :

[0045] (1) Use CuSO4 ·5H 2 O and NiSO 4 ·7H 2 O are mixed at a molar ratio of Ni:Cu = 8:2 to prepare a mixed salt solution with Ni and Cu metal ion concentrations of 2 mol / L; a sodium hydroxide solution (alkali solution) with a concentration of 4 mol / L is prepared, and an ammonia water solution (complexing agent solution) with a concentration of 1.5 mol / L is prepared;

[0046] (2) Under a protective atmosphere, 2 L of a reaction bottom solution with a pH value of 11.5 and an ammonia water concentration of 3 g / L is placed in a reaction kettle, and the reaction temperature is controlled to be maintained at 55 °C with a stirring intensity of 500 rpm; then the Ni and Cu metal salt mixed solution is pumped into the reaction kettle at 20 mL / min, the alkali solution is pumped in at 12 - 13 mL / min, and the ammonia water is pumped in at 5 - 6 mL / min simultaneously for coprecipitation reaction; in the first stage of the coprecipitation reaction, the pH value range is controlled to slowly decrease between 10.6 and 11.5 while keeping the ammonia water concentration unchanged at 3 g / L to control the growth of precursor particles; when the precursor particle D 50 = about 4 μm, the second stage of the coprecipitation reaction is carried out, the pH value is controlled to remain unchanged, and the ammonia concentration is reduced to 2 g / L to control the growth of precursor particles; when the precursor particle D 50 reaches the target particle size of about 5 μm, the feeding is stopped, and after aging, separation, washing, drying, sieving, and demagnetization, the lithium supplement additive precursor Ni 0.8 Cu 0.2 (OH) 2 precursor is obtained. The electron microscope photo of the precursor magnified 10,000 times is as Figure 1 shown. It can be seen from Figure 1 that the lithium supplement additive precursor has good sphericity.

[0047] Step S2, the Ni 0.8 Cu 0.2 (OH) 2 lithium supplement additive precursor and lithium hydroxide are mixed evenly at a molar ratio of (Ni + Cu) / Li = 1:1.95, first sintered at 400 °C for 4 h under a nitrogen sintering atmosphere, then sintered at 700 °C for 14 h, and cooled to room temperature to obtain Li 2 Ni 0.8 Cu 0.2 O 2 lithium supplement additive matrix. The electron microscope photo of the lithium supplement additive matrix magnified 10,000 times is as Figure 2 shown. It can be seen from Figure 2 that the particle morphology uniformity of the lithium supplement additive matrix obtained by sintering the precursor is good and the degree of polycrystallization is relatively high.

[0048] Step S3, diammonium phosphate and Li 2 Ni 0.8 Cu 0.2 O 2 The matrix was added to the ethanol solution at a mass ratio of 2:100, fully stirred, dispersed and dissolved, dried, and pre-sintered at 500 °C for 6 h in a nitrogen atmosphere to obtain Li 2 Ni 0.8 Cu 0.2 O 2 @Li 3 PO 4 .

[0049] Step S4, conducting polymer polyaniline and Li 2 Ni 0.8 Cu 0.2 O 2 @Li 3 PO 4 The mixture was dissolved in ethanol solution at a mass ratio of 3:100, ball milled and mixed, and spray dried by a spray dryer. The spray drying parameters were: inlet temperature 280°C, outlet temperature 110°C, gas flow rate 5m 3 / h; collect the powder to obtain the composite positive electrode lithium supplement additive Li 2 Ni 0.8 Cu 0.2 O 2 @Li 3 PO 4 @C. The electron microscope photo of the composite positive electrode lithium supplement additive magnified 10,000 times is as follows Figure 3 shown. Figure 3 It can be seen that the surface of the composite lithium supplement additive matrix is ​​coated more evenly.

[0050] Example 2

[0051] Different from Example 1, CuSO is used in step S1. 4 ·5H 2 O and NiSO 4 7H 2 O prepares a mixed solution of Ni and Cu metals in a molar ratio of Ni:Cu=9:1, and the preparation methods and parameters of the remaining steps are consistent with those of Example 1, and finally obtains a matrix material nickel copper oxide lithium precursor Ni 0.9 Cu 0.1 (OH) 2 The remaining preparation methods and parameters were the same as those in Example 1.

[0052] Example 3

[0053] Different from Example 1, CuSO is used in step S1. 4 ·5H2 O and NiSO 4 7H 2 O prepares a mixed solution of Ni and Cu metals in a molar ratio of Ni:Cu=6:4, and the preparation methods and parameters of the remaining steps are consistent with those of Example 1, and finally obtains a matrix material nickel copper oxide lithium precursor Ni 0.6 Cu 0.4 (OH) 2 .

[0054] Example 4

[0055] Different from Example 1, in step S2, Ni 0.8 Cu 0.2 (OH) 2 The lithium supplement additive precursor and lithium hydroxide were evenly mixed according to a (Ni+Cu) / Li molar ratio of 1:1.9, and then sintered. The preparation methods and parameters of the remaining steps were consistent with those in Example 1.

[0056] Example 5

[0057] Different from Example 1, in step S2, Ni 0.8 Cu 0.2 (OH) 2 The lithium supplement additive precursor and lithium hydroxide are evenly mixed according to a (Ni+Cu) / Li molar ratio of 1:2.0, and then sintered. The preparation methods and parameters of the remaining steps are consistent with those in Example 1.

[0058] Example 6

[0059] Different from Example 1, in step S3, diammonium phosphate and Li 2 Ni 0.8 Zn 0.2 O 2 The matrix was added to the ethanol solution at a mass ratio of 1:100, fully stirred, dispersed and dissolved, dried, and pre-sintered at 500 °C for 6 h in a nitrogen atmosphere to obtain Li 2 Ni 0.8 Cu 0.2 O 2 @Li 3 PO 4 The preparation methods and parameters of the remaining steps were consistent with those in Example 1.

[0060] Example 7

[0061] Different from Example 1, in step S3, diammonium phosphate and Li 2 Ni 0.8 Zn 0.2 O 2The matrix was added to the ethanol solution at a mass ratio of 3:100, fully stirred, dispersed and dissolved, dried, and pre-sintered at 500 °C for 6 h in a nitrogen atmosphere to obtain Li 2 Ni 0.8 Cu 0.2 O 2 @Li 3 PO 4 The preparation methods and parameters of the remaining steps were consistent with those in Example 1.

[0062] Example 8

[0063] Different from Example 1, in step S4, the conductive polymer polyaniline and Li 2 Ni 0.8 Cu 0.2 O 2 @Li 3 PO 4 Dissolve in ethanol solution at a mass ratio of 1:100, mix by ball milling, and spray dry by a spray dryer;

[0064] Example 9

[0065] Different from Example 1, in step S4, the conductive polymer polyaniline and Li 2 Ni 0.8 Cu 0.2 O 2 @Li3PO 4 The mixture was dissolved in an ethanol solution at a mass ratio of 5:100, ball milled and mixed, and spray dried by a spray dryer. The preparation methods and parameters of the remaining steps were consistent with those of Example 1.

[0066] Comparative Example 1

[0067] Lithium hydroxide, nickel oxide and copper oxide were mixed evenly according to the molar ratio of Li:Ni:Cu=1.95:0.8:0.2, sintered at 400°C for 4h in a nitrogen sintering atmosphere, then sintered at 700°C for 14h, and cooled to room temperature to obtain Li 2 Ni 0.8 Cu 0.2 O 2 Lithium supplements.

[0068] Comparative Example 2

[0069] Different from Example 1, step S3 and step S4 are eliminated, and the preparation methods and parameters of the remaining steps are consistent with those of Example 1 to obtain Li 2 Ni 0.8 Cu 0.2 O 2 Lithium supplements.

[0070] Comparative Example 3

[0071] Different from Example 1, step S4 is cancelled, and the preparation methods and parameters of the remaining steps are the same as those in Example 1, obtaining Li 2 Ni 0.8 Cu 0.2 O 2 @Li 3 PO 4 lithium supplement additive.

[0072] Comparative Example 4

[0073] Different from Example 1, step S3 is cancelled, and the preparation methods and parameters of the remaining steps are the same as those in Example 1, obtaining Li 2 Ni 0.8 Cu 0.2 O 2 @polyaniline lithium supplement additive.

[0074] Comparative Example 5

[0075] Mix LiNi 0.8 Co 0.1 Mn 0.1 O 2 (NCM811), conductive agent SP, and binder PVDF in a mass ratio of 95:2.5:2.5, use NMP as the solvent for slurry mixing, coat it on the fluid aluminum foil, dry it and then press it into a sheet, and then punch the sheet. After drying in an oven at 80 °C for 12 h, it is reserved for use. Use a lithium metal sheet as the negative electrode, and use 1 mol / L LiPF 6 electrolyte, the solvent is a three-component mixed solvent, that is, a mixture of EC:DMC:EMC with a volume ratio of 1:1:1. Use Celgard2400 as the separator, and assemble it into a CR2032 type coin cell. Perform charge and discharge tests within a cut-off voltage range of 2.8 - 4.35 V. The electrochemical performance of the battery products is shown in Table 2.

[0076] Coin cell performance test:

[0077] Respectively mix the lithium supplement additive products in Examples 1 - 9 and Comparative Examples 1 - 4 with the conductive agent SP and the binder (PVDF) in a mass ratio of 90:5:5, add the dispersant N-methylpyrrolidone, adjust it into a slurry, uniformly coat it on the aluminum foil, dry it and then press it into a sheet, and then punch the sheet. After drying in an oven at 80 °C for 12 h, it is reserved for use. Use a lithium metal sheet as the negative electrode, and use 1 mol / L LiPF 6The electrolyte has a solvent that is a ternary mixed solvent, namely a mixture of EC:DMC:EMC with a volume ratio of 1:1:1. Cellgard 2400 is used as the separator. The prepared electrode sheet above is used as the positive electrode to assemble a CR2032 type button cell, and charge-discharge tests are carried out within the cut-off voltage range of 2.8 - 4.35V. The test results are shown in Table 1.

[0078] The lithium supplement additives provided in Examples 1 - 9 and Comparative Examples 1 - 4 are incorporated into the positive electrode material for use. The NCM811 type ternary positive electrode material (other types of ternary positive electrode systems, lithium cobaltate, lithium iron phosphate, lithium manganese iron phosphate, etc. all have the same gain effect), the lithium supplement additive, the binder (PVDF), and the conductive agent SP are mixed at a mass ratio of 93:2:2.5:2.5, and the dispersant N-methylpyrrolidone is added to make a slurry, which is evenly coated on the aluminum foil, dried and pressed into sheets, and then punched. After drying in an oven at 80°C for 12h, it is ready for use. Using a lithium metal sheet as the negative electrode, 1mol / L of LiPF 6 The electrolyte has a solvent that is a ternary mixed solvent, namely a mixture of EC:DMC:EMC with a volume ratio of 1:1:1. Celgard 2400 is used as the separator to assemble a CR2032 type button cell, and charge-discharge tests are carried out within the cut-off voltage range of 2.8 - 4.35V. The test results are shown in Table 2.

[0079] Table 1 Electrochemical performance data of each example and comparative example

[0080]

[0081] Table 2 Electrochemical performance data of each example and comparative example

[0082]

[0083]

[0084] As can be seen from Table 1, compared with the comparative examples, the residual alkali content of the composite positive electrode lithium supplement agent obtained in each example of the present invention is lower, and the charge-discharge specific capacity, initial efficiency, and irreversible specific capacity are higher. It can be seen that the lithium supplement additive precursor prepared by the co-precipitation method first and then the lithium supplement additive matrix obtained by mixing and calcining with the lithium source has more uniform components, can effectively improve the purity of the sintered material, reduce the residual free lithium, reduce side reactions, and thus improve the charge-discharge specific capacity, initial efficiency, and irreversible specific capacity of the lithium supplement agent.

[0085] As can be seen from Table 2, when the composite cathode lithium supplement agents obtained in the embodiments of the present invention are applied to NCM811 system batteries, each embodiment has more excellent cycle performance compared with the comparative example. This is because each embodiment has lower residual alkali compared with the comparative example, which can improve the stability of the slurry during the slurry mixing process and reduce the side reactions during the battery cycling process, thereby improving the cycle stability. The generation of Li 3 PO 4 The coating layer can further consume the residual alkali, and the product Li 3 PO 4 At the same time, it can improve the ionic conductivity. The conductive polymer coating layer can not only effectively improve the conductivity of Li 2 Ni x Cu (1-x) O 2 matrix, but also effectively block its contact with moisture, carbon dioxide, oxygen, etc. in the air, avoiding the deterioration of Li 2 Ni x Cu (1-x) O 2 from oxidation and reaction, thereby improving the cycle stability of the material.

[0086] The present invention has been described in detail above. For those skilled in the art, without departing from the purpose and scope of the present invention and without unnecessary experiments, the present invention can be implemented within a relatively wide range under equivalent parameters, concentrations and conditions. Although specific embodiments of the present invention are given, it should be understood that the present invention can be further improved. In short, according to the principle of the present invention, this application intends to include any changes, uses or improvements to the present invention, including those that depart from the scope disclosed in this application and are made by conventional techniques known in the art. Some basic features can be applied according to the scope of the following appended claims.

Claims

1. A composite positive electrode lithium supplement additive, which comprises, from inside to outside: A substrate, a first coating layer coated on a surface of the substrate, and a second coating layer coated on a surface of the first coating layer; Wherein, the material of the matrix is ​​Li2Ni x Cu (1-x) O2, wherein x is 0.6≤x<1; the first coating layer is a Li3PO4 layer, and the second coating layer is a conductive polymer layer; The general formula of the composite positive electrode lithium supplement additive is Li2Ni x Cu (1-x) O2@Li3PO4@C, where C represents the conductive polymer.

2. The composite positive electrode lithium supplement additive according to claim 1, characterized in that: The matrix is ​​a spherical or quasi-spherical particle with a particle size D50 of 3 to 8 μm; and / or, the mass of the Li3PO4 layer is 1wt% to 3wt% of the mass of the substrate; And / or, the mass of the conductive polymer layer is 1wt% to 5wt% of the total mass of the substrate and the first coating layer; And / or, the conductive polymer is selected from one or more of polyacetylene, polypyrrole, polyaniline, polythiophene, polyfuran, polydopamine and derivatives thereof.

3. The method for preparing the composite positive electrode lithium supplement additive according to claim 1 or 2, comprising the following steps: Step S1, preparing a matrix material nickel copper oxide lithium precursor Ni x Cu (1-x) (OH)2; Step S2, the substrate nickel copper oxide lithium precursor Ni x Cu (1-x) (OH)2 is mixed with lithium source and sintered to obtain Li2Ni x Cu (1-x) O2 matrix; Step S3, Li2Ni x Cu (1-x) The O2 matrix and phosphate are dispersed in solvent 1, dried and sintered to obtain Li2Ni x Cu (1-x) O2@Li3PO4; Step S4, Li2Ni x Cu (1-x) O2@Li3PO4 and conductive polymer are dispersed in solvent 2, ball milled, and spray dried to obtain Li2Ni x Cu (1-x) O2@Li3PO4@C is the composite positive electrode lithium supplement additive.

4. The preparation method according to claim 3, characterized in that: In the step S1, the matrix material nickel copper oxide lithium precursor Ni x Cu (1-x) (OH)2 preparation steps: (1) using a soluble nickel salt and a soluble copper salt in a predetermined molar ratio of Ni:Cu=x:1-x, wherein 0.6≤x<1, to prepare a mixed salt solution of Ni and Cu, so that the total metal ion concentration of the mixed salt solution is 1 to 2 mol / L; preparing an alkali solution with a concentration of 2 to 4 mol / L, and preparing an ammonia solution with a concentration of 1 to 2 mol / L; (2) Under a protective atmosphere, a reaction base solution with a pH value of 11 to 12 and an ammonia concentration of 2 to 4 g / L is prepared and placed in a reaction kettle, the reaction temperature is controlled to be maintained at 50 to 60° C., and the stirring intensity is 400 to 600 rpm; then, a mixed salt solution of Ni and Cu, an alkali solution, and an ammonia solution are simultaneously pumped into the reaction kettle to perform a coprecipitation reaction; in the first stage of the coprecipitation reaction, the pH range is controlled to be slowly decreased between 10.6 and 12, and the ammonia concentration is maintained at 2 to 4 g / L, and the precursor particles are controlled to grow; when the precursor particles D are detected 50 When the target particle size reaches 70% to 90%, the second stage of the coprecipitation reaction is carried out, the pH value is controlled to remain unchanged, the ammonia concentration is 1 to 2 g / L, and the precursor particles are controlled to grow; when the precursor particles D 50 When the target particle size reaches 3 to 8 μm, the feeding is stopped, and the matrix material nickel copper oxide lithium precursor Ni is obtained after aging, separation, washing, drying, sieving and demagnetization. x Cu (1-x) (OH)2.

5. The preparation method according to claim 4, characterized in that: The soluble nickel salt is one or more of nickel sulfate hydrate, nickel chloride, and nickel nitrate hydrate; And / or, the soluble copper salt is one or more hydrates of copper sulfate, copper chloride, and copper nitrate, And / or, the alkali solution is one or a mixture of sodium hydroxide and potassium hydroxide solution; And / or, the flow rate of the Ni and Cu metal salt mixed solution is 20 mL / min, the flow rate of the alkali solution is 12-13 mL / min, and the flow rate of the ammonia water is 5-6 mL / min.

6. The preparation method according to claim 3, characterized in that: In step S2, the lithium source is selected from one or more of lithium hydroxide, lithium carbonate, and lithium oxide; And / or, the lithium source is added in an amount according to a (Ni+Cu):Li molar ratio of 1:1.9 to 2.05; And / or, the gas used for sintering is selected from one or more of nitrogen, argon, carbon monoxide, and hydrogen; the sintering conditions are: pre-sintering at 350-450°C for 4-8h, and then sintering at 600-700°C for 10-18h.

7. The preparation method according to claim 3, characterized in that: In step S3, the phosphate is one or more of monoammonium hydrogen phosphate, diammonium hydrogen phosphate, and triammonium phosphate; And / or, the added mass of the phosphate is Li2Ni x Cu (1-x) 1wt% to 3wt% of the mass of the O2 matrix; And / or, the solvent 1 is one or more of ethanol, methanol, and propanol; And / or, the gas used for sintering is selected from one or more of nitrogen, argon, carbon monoxide, and hydrogen; the sintering conditions are: sintering at 400-600° C. for 4-8 hours.

8. The preparation method according to claim 3, characterized in that: In step S4, the drying is spray drying, and the parameters of the spray drying are: inlet temperature is 280-300°C, outlet temperature is 110-120°C, and air flow rate is 4-6m 3 / h; and / or, the solvent 2 is one or more of ethanol, methanol, and propanol; And / or, the amount of the conductive polymer added is Li2Ni x Cu (1-x) 1wt%~5wt% of O2@Li3PO4 mass.

9. A positive electrode plate, characterized in that: The positive electrode plate comprises the composite positive electrode lithium replenishing additive according to claim 1 or 2, or the composite positive electrode lithium replenishing additive prepared by the method according to any one of claims 3-8.

10. A lithium ion battery, characterized in that: The positive electrode of the lithium-ion battery comprises the positive electrode sheet according to claim 9.

Citation Information

Patent Citations

  • Composite lithium supplement additive and preparation method and application thereof

    CN113036106A

  • Lithium supplement additive for positive electrode material of lithium ion battery, preparation method of lithium supplement additive and positive electrode plate

    CN116364927A

  • Lithium supplement additive, positive pole piece, battery and electric device

    CN117239104A

  • Lithium supplement additive for battery positive electrode, preparation method of lithium supplement additive and battery

    CN118877951A

  • Secondary Battery, Battery Module, Battery Pack and Power Consuming Device

    US20240145793A1